Incidence and direct medical costs of child injuries in Lebanon (2012–2016): Evidence from closed insurance claims analysis - Samar Al-Hajj; Kaitlin R. Maciejewski; Elise Presser; James Dziura; Hani Mowafi (PLoS ONE, 2026)
Despite the Eastern Mediterranean Region (EMR) reporting 20% of the global burden of child injury and one of the highest death rates for child injury (45.5 per 100,000), there are few studies from the region that analyze the costs of these conditions. This study provides an assessment of incidence and direct costs of child injury at hospitals in Lebanon using insurance closed claims. Historical claims data were compiled from the four largest Third-Party Administrators for health insurance companies (> 50% Lebanese insurance market share) for a period of 5 years from 2012–2016. Descriptive statistics and regression modeling were used to assess direct medical costs from hospital treatment of child injuries and to identify risk factors associated with increased costs. A total of 70,640 pediatric patients (<18 years) were treated for 87,102 unique injuries during 86,731 visits totaling $19,466,556.61 during the 5 year study period. Males accounted for almost 2/3 of injured children. Most children (86%) were treated and released from the emergency department but inpatient treatment accounted for over 50% of costs. The most commonly occurring injuries were minor (superficial soft tissue injuries, lacerations, open wounds). However, upper and lower extremity fractures, which accounted for only 7% of injuries, contributed to 28% of costs. Child injuries represent a significant direct medical cost burden in Lebanon, with inpatient treatment contributing a large proportion of expenes. Further prospective studies of child injury should evaluate cost-effectiveness of injury care and to identify opportunities for cost savings through standard treatment protocols for common conditions and injury prevention programs. Further studies are also needed to investigate the indirect and long-term costs of child injuries in Lebanon.